Book review Filozoficzny spór o rolę chrześcijaństwa w kwestii ekologicznej by Ryszard F. Sadowski. Warszawa: TNFS 2015. - Pełka, Marcin (Studia Ecologiae et Bioethicae, 2018)
The summary is not available.